Hegel on beauty - Peters, Julia (Routledge studies in nineteenth-century philosophy, 2015)
While the current philosophical debate surrounding Hegels aesthetics focuses heavily on the philosophers controversial end of art thesis, its participants rarely give attention to Hegels ideas on the nature of beauty and its relation to art. This study seeks to remedy this oversight by placing Hegels views on beauty front and center. Peters asks us to rethink the common assumption that Hegelian beauty is exclusive to art and argues that for Hegel beauty, like art, is subject to historical development. Her careful analysis of Hegels notion of beauty not only has crucial implications for our understanding of the end of art and Hegels aesthetics in general, but also sheds light on other fields of Hegels philosophy, in particular his anthropology and aspects of his ethical thought
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Ästhetik; Hegel, Georg Wilhelm Friedrich